E-government in Canada : transformation for the digital age - Roy, Jeffrey (Ottawa, Ont. : University of Ottawa Press, 2006)
"The rapid expansion of the Internet has fueled the emergence of electronic government at all levels in Canada. E-government's first decade featured online service underpinned by a technically secure infrastructure. This service-security nexus entails internal governance reforms aimed at realizing more customer-centric delivery via integration and coordination across departments and agencies. Yet, as online networking has become more pervasive and public demands for participation rise, pressures for greater openness and accountability intensify. The result is widening experimentation with online democracy. The e-governance focus is thus shifting toward issues of transparency and trust - and new possibilities for re-conceptualizing how power is organized and deployed. In sum, the prospects for digital transformation involve the interplay of these four dimensions: service, security, transparency and trust." "This book identifies the main drivers of e-government, assesses the responses of Canada's public sector to date, and sketches out the major challenges and choices that lie ahead. The findings will be of interest to those studying or working in the world of public sector management and e-governance. Book jacket."--Jacket
Introduction; Part One: Four Main Dimensions of Change; Chapter 1: Service; Chapter 2: Security; Chapter 3: Transparency; Chapter 4: Trust; Part Two: The Canadian Experience; Chapter 5: Government of Canada; Chapter 6: The Provinces; Chapter 7: Local and Intergovernmental Perspectives; Part Three: Looking Ahead; Chapter 8: Organization and Accountability; Chapter 9: Participation and Engagement; Chapter 10: Beyond Canada's Borders; Conclusion; Notes; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y.
Includes bibliographical references (pages 331-349) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Internet in public administration -- Canada; Electronic government information -- Canada; Public administration -- Canada; Organizational change -- Canada; Security, International; Administration publique en ligne -- Canada; Information sur l'État électronique -- Canada; Administration publique (Science) -- Canada; Changement organisationnel -- Canada; Sécurité internationale; POLITICAL SCIENCE -- American Government -- General; Electronic government information; Internet in public administration; Organizational change; Public administration; Security, International; Canada; E-Government; Kanada